2019
DOI: 10.1371/journal.pone.0223907
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cardiorespiratory fitness between preschool children with normal and excess body adipose ~ An observational study

Abstract: ObjectiveOverweight and obesity in preschoolers might develop into childhood and even adulthood obesity. Overweight and obesity have been shown to be negatively related with cardiorespiratory fitness (CRF) in children and adults but few studies did among preschoolers. We aimed to evaluate whether excess body adipose is negatively associated with CRF in both the submaximal and maximal effort of preschool children in exercise testing and to examine if there is difference to achieve maximal effort during exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 45 publications
(58 reference statements)
1
10
0
2
Order By: Relevance
“…Other TM-studies reported maximum heart rates ranging from 194 ± 11/min in 6-year-olds (van der Cammen-van Zijp et al 2010 ), up to an average of nearly 200/min in 5–6-year-old children (LeMura et al 2001 ). However, a study with a comparable age group (5.58 years in girls and 5.86 years in boys) recorded comparable values to our study (178–184/min) (Tuan et al 2019 ). These considerations underline the fact that better cardiopulmonary exertion was reached during the outdoor test compared to the indoor TM test, which was also reflected by the significantly higher values of max , O 2 pulse, and maximum breath rate (BR).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Other TM-studies reported maximum heart rates ranging from 194 ± 11/min in 6-year-olds (van der Cammen-van Zijp et al 2010 ), up to an average of nearly 200/min in 5–6-year-old children (LeMura et al 2001 ). However, a study with a comparable age group (5.58 years in girls and 5.86 years in boys) recorded comparable values to our study (178–184/min) (Tuan et al 2019 ). These considerations underline the fact that better cardiopulmonary exertion was reached during the outdoor test compared to the indoor TM test, which was also reflected by the significantly higher values of max , O 2 pulse, and maximum breath rate (BR).…”
Section: Discussionsupporting
confidence: 84%
“…Average values of 1.05–1.10 have been reported for testing 6–7-year-old-children on a treadmill (Eiberg et al 2005 ). In a TM-study on preschoolers using a ramp protocol instead of a stepwise increase of the workload, RER values as high as 1.03–1.18 were achieved (Tuan et al 2019 ). Our results for the outdoor test are comparable, showing maximum cardiorespiratory exertion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FFM has a powerful influence onVO 2 in children regardless of sexes (10). Our previous study also showed that preschoolers with higher FFMI had better peakVO 2 during treadmill exercise testing (48). Since boys had higher FFMI than girls in all four groups, it is reasonable to find the discrepancy in peakVO 2 between sexes.…”
Section: Discussionmentioning
confidence: 78%
“…In children and adolescents, CRF has been linked to better cognitive function [18], lower adiposity [19], and improved cardiometabolic health [20]. Two previous systematic reviews have suggested that CRF is inversely associated with depressive symptoms in children and adolescents [21,22].…”
Section: Introductionmentioning
confidence: 99%